2020
DOI: 10.1016/j.ijid.2020.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of ten pregnant women with COVID-19 in Wuhan, China: A retrospective study

Abstract: Background: COVID-19 is spreading globally. This study aims to evaluate the clinical characteristics and outcomes of pregnant women confirmed with COVID-19 to provide reference for clinical work. Methods: The clinical features and outcomes of 10 pregnant women confirmed with COVID-19 at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
27

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(117 citation statements)
references
References 19 publications
3
87
0
27
Order By: Relevance
“…The highest preterm percent was in a research investigated cases of pregnant patients with severe coronavirus-2 respiratory infections which was about (90%) (Hantoushzadeh et al, 2020). While premature membrane rupture, the highest incidence was in three studies (Cao et al, 2020;Wu et al, 2020;Zhu et al, 2020). Stillbirth was the least complication, two cases of stillbirth was detected in this review in two studies due to severe maternal infections (Liu et al, 2020c;Lokken et al, 2020).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The highest preterm percent was in a research investigated cases of pregnant patients with severe coronavirus-2 respiratory infections which was about (90%) (Hantoushzadeh et al, 2020). While premature membrane rupture, the highest incidence was in three studies (Cao et al, 2020;Wu et al, 2020;Zhu et al, 2020). Stillbirth was the least complication, two cases of stillbirth was detected in this review in two studies due to severe maternal infections (Liu et al, 2020c;Lokken et al, 2020).…”
Section: Discussionmentioning
confidence: 66%
“…After assessment of abstracts and methods to determine eligible articles; Total 57 articles were excluded (the reasons either no cases included, review articles or symptoms and outcomes were not investigated). The remaining 25 articles are found to be eligible (Breslin et al, 2020a;Breslin et al, 2020b;Cao et al, 2020;Chen et al, 2020a;Chen et al, 2020b;Chen et al, 2020c;Fan et al, 2020;Govind et al, 2020;Hantoushzadeh et al, 2020;Hirshberg et al, 2020;Khan et al, 2020;Liu et al, 2020a;Liu et al, 2020b;Liu et al, 2020c;Lokken et al, 2020;Lu et al, 2020;Pierce-Williams et al, 2020;Polónia-Valente et al, 2020;Wang et al, 2020;Wen et al, 2020;Wu et al, 2020;Xu et al, 2020;Yu et al, 2020;Zambrano et al, 2020;Zhu et al, 2020); they consist of letters, case reports or series, and research articles.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen were case series ( n = 453 pregnancies) [ 23 , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] ], five were cohort studies ( n = 631 pregnancies) [ 17 , [41] , [42] , [43] , [44] ], and one was a case–control study ( n = 16 pregnancies) [ 45 ] ( Supplementary Material Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five of the newborns underwent COVID-19 testing, and none of them were tested positive. The study concluded that COVID-19 is not an indication for caesarean section [41].…”
Section: Clinical Features In Pregnant Womenmentioning
confidence: 92%